Metagenomic insights into host-specific gastroenteritis bacteria in forest rodents of Sarawak, Borneo: implications for one health surveillance of rodent-borne pathogens - Muhammad Amin Iman Azmi; Julius William-Dee; Muhd Amsyari Morni; Nur Afiqah Aqilah Azhar; Nor Al-Shuhadah Sabarudin; Emy Ritta Jinggong; Syamzuraini Zolkapley; Nur Iylia Maisarah Baharom; Muhammad Danish Haqeem; Victor Lee Sien; Asfa Hanis Mohamad Azmi; Madinah Adrus; et al. (BMC Microbiology)
Abstract Rodents are known to act as reservoirs for zoonotic diseases due to their widespread distribution and synanthropic nature. Among these, foodborne pathogens capable of causing gastroenteritis in humans are of particular concern, as rodents can facilitate their transmission through contamination of food sources. Forest-dwelling rodents may harbour bacterial taxa native to their habitat, posing a risk of zoonotic spillover to nearby human settlements. This risk is further heightened by the growing prevalence of ecotourism activities, particularly in tropical countries like Malaysia. In this study, rodent trapping was conducted in selected forested areas adjacent to human settlements across Sarawak. Nanopore sequencing of the full-length 16 S rRNA gene was conducted on faecal DNA from 46 rodent individuals representing seven different species (Maxomys surifer, M. tajuddinii, M. whiteheadi, Niviventer cremoriventer, Rattus tanezumi, R. tiomanicus and Sundamys muelleri). A total of ten bacterial species associated with gastroenteritis were successfully detected. Notable findings in this study include Campylobacter, Salmonella and Shigella species, which are known to cause bacterial gastroenteritis in humans. Also, the presence of certain bacterial taxa in specific rodent genera suggests potential host specificity of foodborne pathogens. This study highlights the potential public health risks caused by rodent-borne bacterial transmission and the importance of monitoring forest rodents as potential reservoirs of zoonotic pathogens.